Frequent expression of the breast differentiation antigen NY-BR-1 in mammary and extramammary Paget's disease - Giger, Olivier; Caduff, Rosmarie; O'Meara, Alix; Diener, Pierre-Andre; Knuth, Alexander; Jäger, Dirk; Moch, Holger; Varga, Zsuzsanna (Pathology international, 2010)
While mammary Paget's disease (MPD) is clearly linked to breast cancer, the histogenesis of extramammary Paget's disease (EMPD) is controversial. Recently NY-BR-1, a differentiation antigen expressed in the breast and in skin adnexal structures was identified. Its protein expression is restricted to normal and neoplastic breast epithelium and to adnexal tumors of the skin. In this study, we examine NY-BR-1 expression by immunohistochemistry in 24 MPD cases with synchronous ductal carcinoma in situ or invasive breast cancer. Results were compared with 26 cases of EMPD of men (n= 4) and women (n= 22) as well as in apoeccrine glands of the axilla and mammary-like glands of the anogenital region. We found NY-BR-1 positivity in 18 of 24 MPD (75%) and in 21 of 26 EMPD (80.8%). All apoeccrine glands of the axilla and mammary-like glands of the anogenital region were NY-BR-1-positive. NY-BR-1 expression is a common finding in MPD and in EMPD. When considering the diagnosis of Paget's disease, NY-BR-1 is a useful diagnostic marker. Furthermore NY-BR-1 positivity in apoeccrine glands of the axilla and anogenital region suggests a potential histogenetic link between these structures and Paget's disease.